2019
DOI: 10.1158/1535-7163.mct-18-0645
|View full text |Cite
|
Sign up to set email alerts
|

TAS-121, A Selective Mutant EGFR Inhibitor, Shows Activity Against Tumors Expressing Various EGFR Mutations Including T790M and Uncommon Mutations G719X

Abstract: TAS-121 is a novel orally active selective covalent inhibitor of the mutant EGFR. We performed preclinical characterization of TAS-121 and compared its efficacy and selectivity for common EGFR mutations (Ex19del and L858R), firstand second-generation EGFR-tyrosine kinase inhibitor (EGFR-TKI) resistance mutation (T790M), and uncommon mutations (G719X and L861Q) with those of other EGFR-TKIs. We also commenced investigation of the clinical benefits of TAS-121. The IC 50 for intracellular EGFR phosphorylation was… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…In contrast, erlotinib did not induce apoptosis, whereas TAS‐121 as well as osimertinib significantly induced apoptosis in the H1975 cell line (Figure 3(e)). These findings confirm that TAS‐121, a third‐generation EGFR‐TKI, overcomes the EGFR T790M‐driven resistance to erlotinib by a mechanism similar to that of osimertinib 16 …”
Section: Resultssupporting
confidence: 66%
See 2 more Smart Citations
“…In contrast, erlotinib did not induce apoptosis, whereas TAS‐121 as well as osimertinib significantly induced apoptosis in the H1975 cell line (Figure 3(e)). These findings confirm that TAS‐121, a third‐generation EGFR‐TKI, overcomes the EGFR T790M‐driven resistance to erlotinib by a mechanism similar to that of osimertinib 16 …”
Section: Resultssupporting
confidence: 66%
“…Here, we report a resistance mechanism of EGFR amplification in a patient with EGFR T790M‐mutated NSCLC who developed acquired resistance to a third‐generation EGFR‐TKI, TAS‐121 16 . We then investigated the role of EGFR amplification in this resistance in vitro.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…5,6 Monoclonal antibodies directed against the extracellular ligand binding domain of the receptor and small molecule tyrosine kinase inhibitors (TKIs) directed against the intracellular adenosine triphosphate (ATP) binding site of the tyrosine kinase domain are two classes of drugs approved for clinical use for targeting EGFR. [7][8][9][10] However, the radiolabeled antibodies clear slowly from circulation which causes dose-limiting hematologic toxicity and requires a longer wait time between injection of the radiolabeled antibody and imaging, 11 whereas the TKIs clear quickly from blood, offering a more flexible time window for imaging.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, one of the most critical steps in the covalent drug discovery process is the effective evaluation of their target specificity and assessment of useful derisking strategies 3,4 . The development of modern 'targeted covalent inhibitors' (TCIs) 5,6 has led to significant progress including the successful launch of several preclinical and clinical studies for covalent EGFR inhibitors, such as the FDA approved afatinib (Giltrif) and osimertinib (Tagrisso), which exhibited promising therapeutic effects against resistant cancer models expressing EGFR mutations [7][8][9] . The systematic studies of TCIs have also revealed that the safety of covalent drugs needs to be evaluated on a case-bycase basis and the complexity of the covalent systems often urge innovative approaches [10][11][12] as necessary complements to conventional preclinical and clinical studies.…”
mentioning
confidence: 99%